2021
DOI: 10.1021/acsaem.1c02310
|View full text |Cite
|
Sign up to set email alerts
|

Effect on 1-Butyl-3 Methylimidazolium Iodide Ionic Liquid in Nonedible Jatropha Oil-Based Polyurethane Acrylate. Tetrabutylammonium Iodide: Lithium Iodide-Based Gel Polymer Electrolyte for Dye-Sensitized Solar Cell Application

Abstract: Improvement of the electrolyte ionic conductivity in DSSCs application is important as it contributes higher solar conversion efficiency. In this article, the polyurethane acrylate (PUA) gel polymer electrolyte (GPE) system was further improved with the addition of an ionic liquid in terms of ionic conductivity and also photovoltaic performance. The PUA GPE system enhanced with 6 wt % of 1-butyl-3-methylimidazolium iodide (BMII) ionic liquid was found to produce the highest improvement (ionic conductivity) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…The carbonyl band can be deconvoluted in three peaks corresponding to the non-hydrogen-bonded C�O (1729 cm −1 ), C�O from amorphous domains bonding with any −NH groups (1697 cm −1 ), and C�O from crystalline domains bonding with −NH groups also from crystalline regions (1682 cm −1 ). 46 Similarly, previous reports 35,46,47 indicate that the position of the three peaks do not significantly shift with the increase of salt concentration, but the intensity of the signals can change substantially. This result indicates that Na + also interacts with the C�O in the SPE, probably coordinating with the oxygen from this group.…”
Section: ■ Results and Discussionsupporting
confidence: 70%
“…The carbonyl band can be deconvoluted in three peaks corresponding to the non-hydrogen-bonded C�O (1729 cm −1 ), C�O from amorphous domains bonding with any −NH groups (1697 cm −1 ), and C�O from crystalline domains bonding with −NH groups also from crystalline regions (1682 cm −1 ). 46 Similarly, previous reports 35,46,47 indicate that the position of the three peaks do not significantly shift with the increase of salt concentration, but the intensity of the signals can change substantially. This result indicates that Na + also interacts with the C�O in the SPE, probably coordinating with the oxygen from this group.…”
Section: ■ Results and Discussionsupporting
confidence: 70%
“…Figure f demonstrates FTIR spectra of the pure or PDMS-free PUA and FTPPS films. The FTIR spectrum of the pristine PUA sample [Figure f­(i)] exhibits fundamental vibrational peaks at ∼1084.6, ∼1236, and ∼1711 cm –1 , which can be assigned to the C–C stretching, amide IIINH and CH, and ester carbonyl CO stretching vibrations, respectively. , Meanwhile, the FTIR spectrum of the FTPPS film [Figure e­(ii)] shows two major peaks at 788 and 1011 cm –1 , which are attributed to CH 3 rocking in Si–(CH 3 ) 2 and Si–O–Si stretching, respectively. In addition, the symmetric stretching and the deformation vibrations of the methyl groupsCH 3 can be found at 1257 and 2961 cm –1 . , These mentioned Raman and FTIR analysis results further validate the successful coating of PDMS on PUA micro-posts by capillary rising.…”
Section: Resultsmentioning
confidence: 99%
“…Semiconductor-sensitized solar devices use low thermal energy (<200 °C) for the proper structure activity of the electrolyte. 56 Most common liquid electrolytes are aqueous I − /I 3 − and S 2− / S n 2− used mostly in dye-sensitized and QDSS solar cells, respectively. An organic solvent accommodating (I − /I 3 − ) electrolyte act as redox mediator in dye-sensitized…”
Section: Functional Electrolyte Photovoltaic Reactions and Redox Pote...mentioning
confidence: 99%
“…De Haro et al 55 developed lignin-functionalized poly-(ethylene glycol) diglycidylether gel electrolyte to achieve photostable DSSC with solar conversion efficiency of 1.50%. Chai et al 56 reported 1-butyl-3-methylimidazolium iodide functionalized polyurethane acrylate gel electrolyte-mediated DSSC with power conversion efficiency of 5.72%. Subramanian et al 57 developed functionalized DSSC by incorporating 1D TiO 2 into PVDF-HFP/PMMA copolymer for LiI electrolyte to achieve solar conversion efficiency of 8.08% owing to excellent entrapping of smaller electrolyte cation (Li + ) across copolymer interchain.…”
Section: Functional Electrolyte Photovoltaic Reactions and Redox Pote...mentioning
confidence: 99%
See 1 more Smart Citation